Bringing Together Indigenous Knowledge and Simulation Modelling to Assess Cumulative Impacts to Indigenous Land Use in Northeastern Alberta, Canada. - Carlson, Matthew; Straker, Justin; Berg, Kevan; Bockstael, Erika; Borle, Emmy; Bindle, Liam; Belisle, Chad; Bonnyman, Matthew; Faichney, Felix; Golden, Denise (Environmental Management, 2025)
The capacity of environmental impact assessment to adequately consider cumulative effects on Indigenous territories in Canada is limited by several deficiencies, including the problematic use of recent or current state as a baseline, adopting a narrow spatial and temporal scope, and marginalizing Indigenous knowledge and experiences. The result is an environmental assessment process that strains Indigenous community resources yet fails to address concerns. Using the Fort McKay Métis Nation (FMMN) of northeastern Alberta as a case study, Indigenous knowledge and simulation modeling were brought together in pursuit of a more comprehensive assessment of cumulative effects on Indigenous land use. Focus group meetings and interviews established that the ability of FMMN members to hunt, fish, trap, and harvest in their territory has rapidly diminished in recent decades, a finding also documented by a simulation that reconstructed landscape changes occurring over the past 120 years across a 103,000 km2 region. The direct footprint from industrial activities, negligible until the 1970s, has since expanded to over 5000 km2, largely due to oil sands and forestry development. Although impacts to moose, fisher, and low-bush cranberry habitat have been relatively minor, opportunity for Indigenous land use has declined substantially due to the effects of industrial footprint, protected areas, and military sites on the accessibility of the land. To facilitate application of this strategic perspective to project assessment, a web application was developed that allows FMMN to assess impacts of development proposals in combination with other past and potential future development relative to a natural baseline.